2012
DOI: 10.1073/pnas.1201994109
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-3 receptor regulates the normal fasting response

Abstract: The melanocortin-3 receptor-deficient (MC3-R −/− ) mouse exhibits mild obesity without hyperphagia or hypometabolism. MC3-R deletion is reported to increase adiposity, reduce lean mass and white adipose tissue inflammation, and increase sensitivity to salt-induced hypertension. We show here that the MC3-R −/− mouse exhibits defective fasting-induced white adipose tissue lipolysis, fasting-induced liver triglyceride accumulation, fasting-induced refeeding, and fasting-induced regulation of the adipostatic and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 57 publications
3
108
3
Order By: Relevance
“…In tumour‐bearing mice, blockade of MC3‐R increased tumour‐induced cachexia, but it did not modify the anorexigenic effect of cancer 30. Furthermore, deletion of the MC3‐R produces an obesity syndrome with a loss in lean mass and increase in adipose mass, without the behavioural hyperphagia seen in the MC4‐R—null mice 31, 32. All these data suggest that MC3‐R activation in experimental cancer or arthritis ameliorates muscle wasting, although it does not prevent anorexia induced by the illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…In tumour‐bearing mice, blockade of MC3‐R increased tumour‐induced cachexia, but it did not modify the anorexigenic effect of cancer 30. Furthermore, deletion of the MC3‐R produces an obesity syndrome with a loss in lean mass and increase in adipose mass, without the behavioural hyperphagia seen in the MC4‐R—null mice 31, 32. All these data suggest that MC3‐R activation in experimental cancer or arthritis ameliorates muscle wasting, although it does not prevent anorexia induced by the illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…103 Additionally, Mc3r -/-mice do not have increased adipose tissue lipolysis, liver triglyceride storage and h ypothalamo-pituitary-adrenal gland axis activation that usually occurs in response to fasting. 104 Finally, POMC products also include β-endorphin, the production of which can be enhanced via a CB1-mediated action that paradoxically links the stimulation of POMC neurons to an increase in food intake. 105 POMC neuron activity is negatively modulated by AgRP cells whose projections follow largely those of the POMC neurons.…”
Section: Autonomic Regulation Of Energy Balancementioning
confidence: 99%
“…It regulates feed efficiency and nutrient partitioning; Mc3r knockout mice have elevated fat mass and reduced lean mass (Butler et al 2000, Chen et al 2000. More recently, several studies have shown that MC3R is required for normal nutrient anticipatory activities and fasting responses (Sutton et al 2008, 2010, Renquist et al 2012. Deletion of Mc3r results in Cushing-like phenotypes with increased basal corticosterone levels and decreased bone density (Renquist et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several studies have shown that MC3R is required for normal nutrient anticipatory activities and fasting responses (Sutton et al 2008, 2010, Renquist et al 2012. Deletion of Mc3r results in Cushing-like phenotypes with increased basal corticosterone levels and decreased bone density (Renquist et al 2012). Consistent with an important role of MC3R in regulating energy homeostasis, mutations in MC3R have been identified to be associated with human obesity or adiposity (Tao 2010) as well as lung diseases including tuberculosis and cystic fibrosis (Cooke et al 2008, Wright et al 2011.…”
Section: Introductionmentioning
confidence: 99%